Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan Manufaktur Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Maria Tali Keytimu; Antonius Philipus Kurniawan; Elisabet Luju (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This research was conducted to examine the effect of capital structure and profitability on the value of food and beverage manufacturing companies listed on the Indonesia Stock Exchange.The population in this study was 12 and the research sample was 4 manufacturing companies the sampling technique in this study was purposive. Data analysis using classical assumption test with normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Correlation analysis and conduct multiple linear regression analysis hypothesis test. F statistical test and Tstatistical test. Descriptive analysis results : 1. DER showed that every RP 1 liability could be fulfilled with RP 0.8634596 total equaity 2. ROA obtained an average of 0.76771 of total assets 3. PBV had an average of RP 0.414877 of the total share price. The statistical results of the t-test showed that the capital structure (XI does not have a significant impact on the company’s value (Y). The results of the determination analysis (RZ) show that the capital structure and profitability variables can explain the variation in the rise and fall of the value of food and beverage manufacturing companies listed on the indonesia stock Exchange by 56%.